Antibiotic Consumption Patterns in European Countries Are Associated with the Prevalence of Parkinson's Disease; the Possible Augmenting Role of the Narrow-Spectrum Penicillin - Gábor Ternák; Márton Németh; Martin Rozanovic; Gergely Márovics; Lajos Bogár (MDPI AG, 2022)
Parkinson's disease: Parkinson's disease (PD) is the second-most common neurodegenerative disease, affecting at least 0.3% of the worldwide population and over 3% of those over 80 years old. According to recent research (2018), in 2016, 6.1 million (95% uncertainty interval (UI) 5.0-7.3) individuals had Parkinson's disease globally, compared with 2.5 million (2.0-3.0) in 1990. The pandemic-like spreading of PD is considered a slow-moving disaster. Most recent studies indicated the possible role of an altered microbiome, dysbiosis, in the development of PD, which occurs long before the clinical diagnosis of PD. Antibiotics are considered as major disruptors of the intestinal flora and we have hypothesized that, as different classes of antibiotics might induce different dysbiosis, certain classes of antibiotics could trigger the PD-related dysbiosis as well. Comparative analyses were performed between the average yearly antibiotic consumption of 30 European countries (1997-2016) and the PD prevalence database (estimated for 2016). We divided the time frame of antibiotic consumption of 1997-2016 into four subsections to estimate the possible time lapse between antibiotic exposure and the prevalence, prevalence change, and PD-related death rates estimated for 2016. Our results indicated that countries with high consumption of narrow-spectrum penicillin experienced a higher increase in PD prevalence than the others. Countries reporting a decline in PD from 1990 to 2016 demonstrated a reduction in the consumption of narrow-spectrum penicillin in this period.